Analysis of the impact of financial performance on stock prices with company size as a moderating variable in energy sector companies listed on the idx from 2021 to 2023 - Nafisah, Aura Fitria; Bayu Bawono, Andy Dwi (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of financial performance on the share prices of energy sector companies on the Indonesia Stock Exchange. The data used in this research is secondary data, taken from the 2021 to 2023 annual financial reports of energy sector companies listed on the IDX. The sampling method uses purposive sampling. The sample consists of 37 companies. The analytical tool used to test the hypothesis is multiple linear regression analysis using SPSS version 30. The results of this study show that the Current ratio, Return On Assets, Debt To Equity Ratio, and Total Asset Turnover have no effect on stock prices, Current ratio, Return On Assets, with Total Asset Turnover and company size as a moderating variable do not have a significant effect on stock prices. Meanwhile, the Debt To Equity Ratio with company size as a moderating variable has a significant effect on share prices